Strategi Berdakwah di Rumah Tahanan Negara (Studi Kasus Strategi Dakwah Profesor Salmadanis Bagi Warga Binaan Pemasyarakatan di Rumah Tahanan Negara Klas IIB Padang) - ASRUL HARAHAP (STAI Hubbulwathan Duri, 2018)
Da'wah to the inmates is not an easy matter, but da'wah is needed to make them aware. In order for da'wah to be delivered to the assisted citizens to change their attitudes, then the right da'wah strategy is needed and about the goals. Basically the people who are inmates in Prison Houses are people who are subject to criminal sanctions as a result of their behavior, therefore detention houses or prisons are used as psychological shock to what they bear from situations of social alienation to improve themselves.